Recurrent Candida Parapsilopsis Corneal Ulcer cum Hypopion: A Case Report: Poster Presentation - Case Report - Resident - Septian Dwi Prabowo; Ismi Zuhria (Majalah Oftalmologi Indonesia, 2023)
Introduction : Candida is common in tropical and subtropical climes estimated for 20-60% of all culture-positive corneal infection. Over the past two-decades, candida parapsilosis has become a common opportunistic fungal pathogen. Case Illustration : A-60-years-old-man, came with redness and pain in the left eye since one month ago after working at field. In the left eye, visual acuity was hand movement, palpebra was spasm and oedema, conjunctiva was hyperaemia, hazy, feathery edge and fluorescein test were positive in paracentral corneal 6x7 mm and hypopyon in anterior chamber. KOH staining revealed yeast, corneal scrapping revealed candida parapsilopsis, and antifungal sensitive to fluconazole. Fluconazole intravenous 200mg 2-times-a-day, moxifloxacin eyedrop loading dose, fluconazole eyedrop fortified every-one- hour, atropine 1% eyedrop 2-times-a-day, artificial tears eyedrop every-one-hour was administered.In the fifth-day, hypopyon was improved, and patient was discharged. Tenth-days after, patient felt pain and hypopyon raised 4mm. Debridement in the ulcer, and therapy was continued. Two weeks later, hypopyon was less than 1 mm, and pain was relieved. Discussion : There was clinically improvement using antifungal therapy. Recurrent hypopyon was happen, and mechanical debridement in the ulcer was administered. In four-times within two-weeks, hypopyon was improved. Although, initial treatment was antibiotics until microbiological confirmation, antifungal therapy, combined with mechanical eradication of fungal filaments could be administered for fungal corneal ulcer. Conclusion : In this case, combination of antifungal therapy with mechanical debridement could be the right choice to treat candida parapsilopsis corneal ulcer. Better outcomes can be achieved and complications can be avoided with appropriate diagnosis and efficient therapy.